Comparison of sudden cardiac arrests/deaths in South African & European professional football leagues: risks, incidence, and preventive measure: A systematic review - Maqina, L. (BASES Conference 2024, 2024)
Background: Football, commonly known as soccer, is one of the most popular sports in the world with millions of players and supporters. Sudden cardiac arrest/death(s) (SCA/SCD) are rare but traumatising incidents in sports, particularly in football. SCD are the leading cause of death in young athletes, and this raise concerns in football. Soccer is a physically demanding exercise. Athletes with an undiagnosed cardiovascular abnorm ality may be at a risk for SCA/SCD.